Institute of Metals Division - The System Tantalum-Titanium- Zirconium-Oxygen at 1500°C - Michael Hoch; Daniel B. Butrymowicz (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1964)
The isothermal section of the Ta-Ti-Zr-0 system at 1500°C was investigated using X-ray diffraction and rrzetallographic techniques. Up to 71.4 at, pct 0 the system contains nine four -phase regions. Zsopleths at 10, 20, 30, 40, 50, and 60 at. pct 0 were constructed. The purpose of this investigation was to determine the general shape of the quaternary equilibrium phase diagram of tantalum, titanium, zirconium, and oxygen at 1500°C. The system was truncated at 66.7 at. pct 0 on the Ti-0 and Zr-0 binaries and at 71.4 at. pct 0 on the Ta-0 binary. The Ti-Zr-0 system was investigated in this laboratory.' The binary systems of interest have been compiled and discussed by Hansen and Anderk, chmidt, Hayes, Roberson, and asche, and Hoch and athur.' EQUIPMENT The Same equipment as that for the study of the Nb(Cb)-Ti-Zr-0 system was used.' The X-ray dif- fraction patterns were analyzed with the help of the ASTM card set7 and NBS circulars.' MATERIALS The tantalum powder (99 pct pure), the titanium powder (99.6 pct pure), the tantalum pentoxide, and the zirconium dioxide used in this study were purchased from the Fairmont Chemical Co., Newark, N.J. The zirconium powder (99.4 pct pure) was obtained from the Charles Hardy Co., Inc., New York. Reagent-grade titanium dioxide was purchased from the Matheson Co., Inc., Norwood, Ohio. The oxides were dried in air at 700°C for 24 hr before use. Though the materials used were not "hyper-pure", the impurities present do not affect the results (lattice parameters, phase boundaries), within the experimental accuracy. PROCEDURE The samples were heated by induction in a vacuum furnace, and examined metallographically and by X-ray diffraction at room temperature. The procedure was the same as that in the Nb(Cb)-Ti-Zr-O work,' EXPERIMENTAL RESULTS AND DISCUSSION OF DATA A four-component system can be represented by a tetrahedron at a single temperature and pressure